Деякі результати реінтродукції Valeriana officinalis s.l. на південному сході України - Ptytsya, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Results of the experiment on Valeriana officinalis s.l. vanishing populations renuval on the South-East of Ukraine by the reintroduction method have been given. It has been revealed that the species artifical populations forming by the transplanting method is the more effective as compared to seed method.